Stakeholder perspectives on antenatal depression and the potential for psychological intervention in rural Ethiopia: a qualitative study - Tesera Bitew; Roxanne Keynejad; Simone Honikman; Katherine Sorsdahl; Bronwyn Myers; Abebaw Fekadu; Charlotte Hanlon (BMC, 2020)
Abstract Background Psychological interventions for antenatal depression are an integral part of evidence-based care but need to be contextualised for respective sociocultural settings. In this study, we aimed to understand women and healthcare workers' (HCWs) perspectives of antenatal depression, their treatment preferences and potential acceptability and feasibility of psychological interventions in the rural Ethiopian context. Methods In-depth interviews were conducted with women who had previously scored above the locally validated cut-off (five or more) on the Patient Health Questionnaire during pregnancy (n = 8), primary healthcare workers (HCWs; nurses, midwives and health officers) (n = 8) and community-based health extension workers (n = 7). Translated interview transcripts were analysed using thematic analysis. Results Women expressed their distress largely through somatic complaints, such as a headache and feeling weak. Facility and community-based HCWs suspected antenatal depression when women reported reduced appetite, sleep problems, difficulty bonding with the baby, or if they refused to breast-feed or were poorly engaged with antenatal care. Both women and HCWs perceived depression as a reaction ("thinking too much") to social adversities such as poverty, marital conflict, perinatal complications and losses. Depressive symptoms and social adversities were often attributed to spiritual causes. Women awaited God's will in isolation at home or talked to neighbours as coping mechanisms. HCWs' motivation to provide help, the availability of integrated primary mental health care and a culture among women of seeking advice were potential facilitators for acceptability of a psychological intervention. Fears of being seen publicly during pregnancy, domestic and farm workload and staff shortages in primary healthcare were potential barriers to acceptability of the intervention. Antenatal care providers such as midwives were considered best placed to deliver interventions, given their close interaction with women during pregnancy. Conclusions Women and HCWs in rural Ethiopia linked depressive symptoms in pregnancy with social adversities, suggesting that interventions which help women cope with real-world difficulties may be acceptable. Intervention design should accommodate the identified facilitators and barriers to implementation.